The Role of Character Education on the Discipline and Learning Outcomes of Madrasah Tsanawiyah Students - Masfufah Masfufah; Didit Darmawan (Molang: Journal Islamic Education, 2023)
Now education has been recognized as having a major role as social and moral capital and ensuring the improvement of the quality of life of future generations. Therefore, it is important to encourage positive experiences in educational classrooms. The educational environment is one of the contexts that most affect the culture and character of students. For this reason, this study intends to analyze and understand the role of character education in shaping the discipline and learning outcomes of MTs students. There were 123 respondents who came from MTs students and were selected using the purposive sampling technique. Data collection is carried out through the distribution of questionnaires and documentation of student learning outcomes. The data analysis in this study uses multiple linear regression analysis techniques. The results of the study show that character education associated with discipline has a positive and significant influence. Character education is also related to learning outcomes having a positive and significant influence. Students who have the character of discipline, responsibility, honesty, and care for the learning environment tend to show better learning behavior so that it has an impact on improving learning outcomes. Overall, character education has a positive influence on MTs students in forming discipline attitudes, increasing learning motivation, and supporting students' academic achievements. Thus, the implementation of character education needs to continue to be strengthened through learning, teacher examples, and a conducive school culture to create a generation with character and achievement.